Personality traits in online game addiction in Denpasar - I Gusti Rai Putra Wiguna; Cokorda Bagus Jaya Lesmana; I Gde Raka Widiana (Journal of Clinical and Cultural Psychiatry, 2020)
Background: One type of psychiatric disorder that is still controversial is online game addiction. A massively multiplayer online role-playing game (MMORPG) has the highest prevalence of game addiction, especially in Asian countries. The goal of this study was to see the correlation between personality traits, openness, conscientiousness, extraversion, agreeableness, and neuroticism with the occurrence of online game addiction.Methods: A cross-sectional study was conducted on 248 adult online games players throughout Denpasar through proportional stratified random sampling randomization by searching for online game addiction status based on Indonesian Game Online Questionnaires’ (IGOQ) and Five-Factor Personality Traits based on the International Personality Item Pool (IPIP NEO- PI).Results: The prevalence rate of online game addiction in online game center players in Denpasar obtained 27%, the majority are students, male, Hindu, Bali. On average, playing more than 35 hours a week and playing more than 12 hours in 1 session. From the analysis of personality traits, it was found that the traits of conscientiousness had a protective relationship between the occurrence of online game addiction with adjusted Odd Ratio was 0.895 (p <0.001).Conclusion: Personality traits tests focused on trait conscientiousness can be used as a screening for potential addictions.